The effectiveness of internship programs towards developing employees for domestic and international demands / Muhd Khairi Abu Bakar - Abu Bakar, Muhd Khairi (Faculty of Business and Management, 2010)
These case studies explore the effectiveness of internship programs towards developing employees for domestic and international demands Cyberview Sdn. Bhd and the theories. This internship programme objectives of the Company should provide the achieve target and goal, the organization clear about mission and vision. Focused on determining the prevalence and perceived effectiveness of internship program in company and organization to make this kind of plan success and running smooth. Next, the Company and candidates should evaluating the internship program based upon these goals is essential to measuring the development in the organization. Often the only measurement criteria for an event are the profit at the end of the day. To make sure all team member understand definition of development performance to improve and perform better.